0006 The Pharmacokinetics and Pharmacodynamics of SM-1. (27th April 2018) - Dahl, T; Roth, T; Scheinin, M; Suopanki-Lalowski, J; Valge, M; Puhakka, A; Mikola, H; Lovró, Z; Meierjohann, A; Vuorilehto, L; Chen, L
Abstract: Introduction: The most common form of sleep disturbance is transient insomnia, and in parallel the most common pattern of use for hypnotic medications is short-term use. We report here the results of a daytime sedation clinical trial with a staged-release combination drug product, SM-1, comprised of immediate release diphenhydramine 50 mg, delayed-release zolpidem 5 mg, and delayed-release lorazepam 0.5 mg. Methods: This was a double blind, placebo controlled, randomized, crossover study to assess the pharmacokinetics and pharmacodynamics of SM-1 in 24 healthy volunteers. Blood samples were collected prior to and at the following time points after the dose: 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 5, 6, 7, 8, 10, 12, 16 and 24 hours to determine the concentrations of diphenhydramine, zolpidem and lorazepam in plasma. Sedative drug effects were assessed with visual analogue scales (VAS) and the digit symbol substitution test (DSST) prior to and at the following time points after dosing: 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 5, 6, 7, 8, 10, 12 and 24 hours. Memory acquisition and immediate recall were assessed with a word list test at 1, 2, 4, 6, 8, 10 and 12 hours after the dose administration. Electroencephalographic (EEG) recording were carried out prior to and at the following time points after the dose: 1, 2, 4, 6, 8, 10 and 12 hours, for off-line analysis of the proportion of beta frequency amplitude in the EEG spectrum. Results: The drug combination was well tolerated, as evidenced by similar number and severity of adverse events following administration of SM-1 and placebo. The pharmacodynamic profile of SM-1 showed onset of activity, as determined by subjective, performance, and EEG surrogates for sedation, at 0.5–1 hour post-dose, lasting about 7–7.5 hours. Pharmacokinetic profiles showed that the shapes of the plasma concentration curves for the two delayed-release components were altered compared with published data with unmodified drugs, while for all three agents the exposure values obtained with the combination product are in good agreement with published or historical values of the drugs given individually. Conclusion: Support (If Any):